Pengembangan LKPD Menulis Teks Cerita Fantasi Berbasis Metakognitif Peserta Didik Kelas VII - Merina Tri Rahma Okta; Nurlaksana Eko Rusminto; Munaris Munaris (Universitas Lampung, 2018)
This research aims (1) to produce LKPD write text-based Fantasy Story Metacognitive, (2) to describe eligibility of materials LKPD write text-based Fantasy Story Metacognitive developed based on material experts, media experts, practitioners, teachers and students. This research adapts development research according to Brog and Gall. This research was conducted at three schools, including: Junior High School of Global Madani Bandar Lampung, Junior High School of 13 Bandar Lampung, and Junior High School of IT Baitul Jannah Bandar Lampung in the academic year 2017/2018. Metacognitive aspects contained in these materials include: planning skills, monitoring skills, and evaluation skill. The results of this research resulted (1)learning materials in the form of